PENGARUH PENUNDAAN PEMERIKSAAN WIDAL METODE SLIDE PADA PASIEN DEMAM TIFOID DI RSU ANNA MEDIKA MADURA - Masfufah, Ainun; Najiyah, Fitriyatin; Alfia, Luluk (NHM PRESS, 2020)
Widal examination is an agglutination examination using suspension of Salmoella typhi and S. Paratyphi as antigens to detect the presence of antibodies against Salmoella typhi or S. Paratyphi in patient's serum. Salmonella infections in humans can vary in the form of infections that can heal itself (gastroenteritis), but can also be a serious case if there is a systemic spread (enteric fever). The purpose of this study was to determine the effect of delaying the slide method widal examination in typhoid fever patients at Anna Medika Madura General Hospital. This research uses a quasi-experimental method (pre-experiment / quasi experimental design). The variable of this study is the effect of the delay of the Widal Slide Method examination. The population was 25 patients at Anna Medika Madura Public Hospital, while the sample was 25 respondents. The sampling technique used was purposive sampling. The analysis technique used in this study was the Repeated Anova Measure test. The statistical test results of this study were obtained the level of confidence α = 5% (0.05) with P value> α 0.05 ie P Value = 0.354 then H0 received H1 was rejected, so it can be concluded that there was no effect of delaying the widal slide examination method in typhoid fever patients at Anna Medika Madura Public Hospital. Based on the results of the study, it is expected for further researchers to try to conduct widal examination using plasma without being separated from the tube with temperatures above 25 ° C